2019
DOI: 10.1007/s00262-019-02333-9
|View full text |Cite
|
Sign up to set email alerts
|

An HER2 DNA vaccine with evolution-selected amino acid substitutions reveals a fundamental principle for cancer vaccine formulation in HER2 transgenic mice

Abstract: Enhancement of endogenous immunity to tumor-associated self-antigens and neoantigens is the goal of preventive vaccination. Toward this goal, we compared the efficacy of the following HER2 DNA vaccine constructs: vaccines encoding wild-type HER2, hybrid HER2 vaccines consisting of human HER2 and rat Neu, HER2 vaccines with single residue substitutions and a novel human HER2 DNA vaccine, ph(es)E2TM. ph(es)E2TM was designed to contain five evolution-selected substitutions: M198V, Q398R, F425L, H473R and A622T th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 44 publications
0
1
0
Order By: Relevance
“…This cancer vaccine has been developed against the tyrosine-kinase receptor HER2, which is considered an ideal target in cancer immunotherapy due to its crucial role in the epithelial transformation and its selective overexpression in cancer tissues, such as breast cancer. Since HER2 is exposed on the cell membrane, it can be targeted by both antibodies and cell-mediated immunity. It was previously reported that pVAX-hECTM is able to induce an antitumor immune response in breast cancer preclinical models when administered by electroporation. Thus, we encapsulated the DNA vaccine into LNP15, while the less-effective formulation (i.e., LNP13) was used as a negative control. Immunofluorescence experiments reported in Figures and in S1 in the Supporting Information were aimed at demonstrating that transiently transfected cells can express the oncoantigen HER2 encoded by the DNA vaccine and display it on the cell surface.…”
Section: Resultsmentioning
confidence: 99%
“…This cancer vaccine has been developed against the tyrosine-kinase receptor HER2, which is considered an ideal target in cancer immunotherapy due to its crucial role in the epithelial transformation and its selective overexpression in cancer tissues, such as breast cancer. Since HER2 is exposed on the cell membrane, it can be targeted by both antibodies and cell-mediated immunity. It was previously reported that pVAX-hECTM is able to induce an antitumor immune response in breast cancer preclinical models when administered by electroporation. Thus, we encapsulated the DNA vaccine into LNP15, while the less-effective formulation (i.e., LNP13) was used as a negative control. Immunofluorescence experiments reported in Figures and in S1 in the Supporting Information were aimed at demonstrating that transiently transfected cells can express the oncoantigen HER2 encoded by the DNA vaccine and display it on the cell surface.…”
Section: Resultsmentioning
confidence: 99%